1997
DOI: 10.1242/jcs.110.7.861
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin provides a conduit for fibroblast transmigration from collagenous stroma into fibrin clot provisional matrix

Abstract: After injury, the wound space is filled with a fibrin/fibronectin clot containing growth factors released by platelets and monocytes. In response to these factors, fibroblasts migrate into the fibrin clot and contribute to the formation of granulation tissue. The functional mechanisms allowing fibroblasts to leave the collagenous matrix of normal connective tissue and invade the provisional matrix of the fibrin clot have not been fully defined. To investigate these mechanisms we established a new in vitro mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…It has been demonstrated that PDGF-BB serves as both a chemoattractant and in establishing a haptotactic gradient for HDF transmigration from peripheral tissues to the wound surface and promotes the vitality and function of HDFs [ 19 , 20 ]. We detected the content of PDGF-BB in IT MSC-CM by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that PDGF-BB serves as both a chemoattractant and in establishing a haptotactic gradient for HDF transmigration from peripheral tissues to the wound surface and promotes the vitality and function of HDFs [ 19 , 20 ]. We detected the content of PDGF-BB in IT MSC-CM by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that platelet concentrates could provide a supportive matrix for circulating stem/progenitor cells [68,69], which are recruited from blood to injured tissue by a variety of signaling molecules [5,70], including VEGF, MMP, PDGF-B, and Ang-2 [16,[71][72][73]. Growing evidence points to the role of circulating CD34 positive cells, such as EPCs, in vascular maintenance, neovascularization, and angiogenesis [3][4][5][6]74].…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin and PDGF play a role in fibroblast migration to fibrin clots in collagen hydrogels. 48 Further, plasminogen expression aids in fibroblast invasion of fibrin, but may not be essential. Evidence suggests that the expression of other proteinases can overcome plasminogen deficiency.…”
Section: Fibrinmentioning
confidence: 99%